«Үлкен бестік» бес факторлы тұлғалық сауалнамасының қазақ тілді нұсқасын бейімдеу туралы (The Journal of Psychology and Sociology, 2019)
The article is devoted to adaptation and validization of Kazakh version of well-known personality questionnaire “Big Five” (created by McCrae and Costa, 1983-1985). “Big Five” questionnaire is based on fife-factor model of personality (FFM) and includes 75 questions to measure Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness to Experience. Participants were 104 (26 male, 78 female) volunteers students of the Al-Farabi Kazakh National University. Inclusion criteria was requirement of high school graduation in Kazakh language. All participants were acknowledged with experiment goals with written information and signed informed consent form. Study was approved by the Ethnics Committee of the Medical Faculty of the Al-Farabi Kazakh National University. The purpose of the study was adaptation of the Kazakh version of the “Big Five” questionnaire to be able to use this questionnaire in future for psychophysiological study of depressive states. IBM SPSS21 was used for statistical analyses of Cronbach’s alpha for each questionnaire scale. Results showed significatе internal consistency of the Kazakh version of the “BigFive” which allows us to use this questionnaire in future studies.Key words: Personality, Extraversion, Cronbach’s Alpha, Neuroticism.